Evaluating the Impact of Government Policies on Circular Economy Adoption in the Construction Sector - Hoareau, Carol Emilly; Tam, Nicholas (Civil and Sustainable Urban Engineering, 2024)
The construction sector is both essential for global economic progress and one of the largest contributors to pollution, resource depletion, and energy consumption. Given the urgent need to adopt more sustainable practices, governments in developed countries have introduced policies aimed at fostering a circular economy in this sector. These policies emphasize the use of green materials to reduce resource consumption, energy use, and greenhouse gas emissions, aligning with global sustainability goals. The waste hierarchy further governs these policies, prioritizing waste reduction, reuse, and recycling. This study analyzes the effectiveness of these government policies in promoting circular economy principles, particularly the adoption of green materials in the construction industry. Our findings reveal that while these policies have led to measurable reductions in energy consumption and emissions, the extent of green material adoption varies significantly across countries. Key factors influencing this variation include economic incentives, regulatory enforcement, and the level of industry acceptance of green technologies. One of the most important results of this study is the identification of significant gaps between policy intent and actual industry practices. In many cases, green materials, despite their favorable characteristics, have not been widely implemented due to economic, technical, and market barriers. These findings underscore the need for stronger government incentives and more consistent policy enforcement to drive broader adoption of sustainable practices. Future studies should focus on overcoming these barriers, exploring the long-term economic impacts of green material adoption, and evaluating how policy frameworks can be optimized to ensure more widespread.